Síndrome de Burnout en docentes universitarios (2015)
Introduction: Identify Burnout or physical fatigue in workers engaged in teaching it is of utmost importance for the development of the proposed improvement of working conditions. Objetive: To determine Burnout in teachers of the Faculty of Nursing at the Cooperative University of Colombia in Santa Marta. Methodology: Descriptive correlational study with a quantitative approach, in which a sample of 30 teachers out of a total population of 56, non-probabilistic sample selection was chosen. Data collection was done through the Instrument Maslach Burnout Inventory (MBI), which measures emotional exhaustion, depersonalization and personal development. Results: The 66.6 % had low emotional exhaustion and 26.6 % Average emotional exhaustion. 96 % low level of depersonalization and 80 % higher level of personal fulfillment; positive correlation between depersonalization / length of service was evident. Results may indicate that the presentation of Burnout is directly proportional to the elapsed service. Conclusions: The teaching in the nursing staff represents a risk condition for the presentation Burnout. © 2015, Editorial Ciencias Medicas. All rights reserved.